Performance Optimization of Erbium Doped Fiber Amplifier in Wavelength Division Multiplexing System for Long Haul Transmission - Zaiton, A.M.; Lee, C.T.; Irda, H. (2011)
This research explores how to optimize the Erbium Doped Fiber Amplifier that being used in Wavelength Division Multiplexing for Long Haul Optical Transmission System. The paper explains the fundamental knowledge, the characteristics of Erbium Doped Fiber Amplifier and the simulation process involved in completing the research. The methods used to achieve the objectives are also clarified throughout the report.